Dual-Functional Graphene Oxide-Based Photothermal Materials with Aligned Channels and Oleophobicity for Efficient Solar Steam Generation - Chen, Lihua (Langmuir : the ACS journal of surfaces and colloids, 2021)
Desalination by solar steam generation (SSG) has emerged as one of the most efficient approaches to address the issue of global water shortage. In this work, novel graphene oxide (GO)-based solar steam generators (GO-SSGs) with aligned channels were prepared by directional freezing and simple carbonization of a hydrogel composed of GO and poly(vinyl alcohol) (PVA). Benefitting from their excellent light absorption (light absorption efficiency exceeds 94%), better thermal insulation (thermal conductivity, 0.259 W/(m K)), and suitable porous structure, which facilitates rapid water transportation, the GO-SSGs show superior SSG performance with a high solar energy conversion efficiency of up to 92% achieved under an irradiation of 1.0 kW/m2. Interestingly, uniquely aligned channels endow them with good salt-rejection performance; the solar energy conversion efficiency of GO-SSGs in 20 wt % NaCl, KCl, and MgCl2 brine can reach more than 85%. To improve their antifouling performance, a chemically hydrophilic and oleophobic modification was conducted, making it possible to run SSG even in oily wastewater; for instance, a solar energy conversion efficiency of 84% was obtained in an aqueous solution containing 10 wt % n-hexadecane. Compared with the existing photothermal materials, these materials show advantages of simple manufacture, high SSG efficiency, superior salt tolerance, and antifouling performance, which make them promising candidates as a kind of new high-performance photothermal materials for desalination even in oily wastewater, thus further expanding the scope of their practical SSG application